2016
DOI: 10.1016/j.matdes.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and antifouling behaviour of a carbon nanotube membrane

Abstract: In this work, a novel approach is used to synthesize an iron oxide doped carbon nanotube (CNT) membrane, with the goal of fully utilizing the unique properties of CNTs. No binder is used for the synthesis of the membrane; instead, iron oxide particles serve as a binding agent for holding the CNTs together after sintering at high temperature. The produced membrane exhibited a high water flux and strong fouling resistance. In the first step, CNTs were impregnated with various loadings of iron oxide (1, 10, 20, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…In this method the weight of dry and wet samples are measured and then difference is taken of both dry and wet samples weight. Barrett-Joyner-Halenda (BJH) model has been used for pore size distribution of nanoparticles of titania and zirconia [232][233][234]. Brunauer-Emmett-Teller (BET) model is used to analyze porosity and pore size surface area of nanoparticles of metals or their oxides and composites.…”
Section: Bubble Point Methodsmentioning
confidence: 99%
“…In this method the weight of dry and wet samples are measured and then difference is taken of both dry and wet samples weight. Barrett-Joyner-Halenda (BJH) model has been used for pore size distribution of nanoparticles of titania and zirconia [232][233][234]. Brunauer-Emmett-Teller (BET) model is used to analyze porosity and pore size surface area of nanoparticles of metals or their oxides and composites.…”
Section: Bubble Point Methodsmentioning
confidence: 99%
“…The TGA result shown in Figure 4 exhibits 10 wt% weight reduction at 343 ∘ C which may be due to the presence of amorphous carbons and structural defects; the sample then begins to decompose rapidly from 90 wt% to 4.6 wt% beginning from 343 ∘ C to 490 ∘ C, respectively; this suggests the presence of carbon nanomaterials. The DTGA result displays a major peak observed at 421.5 ∘ C at 50 wt% which does not seem high enough for CNTs in comparison with results obtained by other research groups; however, this result is justifiable since it has been shown that the presence of iron oxide in CNTs sample may result in lower decomposition temperature [25]. Based on this result we may presume the presence of carbon nanomaterial as a main outcome of the experiment [26].…”
Section: Resultsmentioning
confidence: 63%
“…This may be due to the fact that the impregnation of iron oxide nanoparticles on CNTs serves as an impurity, hence leading to steep weight loss at lower temperature [31]. Additionally, iron oxide nanoparticles reduced the agglomeration of CNTs as shown in SEM images that might also led to easy degradation [32]. Around 1% weight of the material was left at the end of the analysis for pure CNTs.…”
Section: Resultsmentioning
confidence: 99%